Effect of Stocking Density Stress on the Hematological Profile of Oncorhynchus Mykiss in KashmirTrout Raceways - Charoo, Samina Qadir (Journal of Science and Technology, 2014)
The present research aimed at the investigation into the effect of stocking density on the hematological response of Oncorhynchus mykiss maintained in flow through condition. The stock having a weight of 520.22 ± 48.20 g and 580.25± 52.2 g were stocked in flow through FRP tanks at the stocking density of 38 kg/m3 and 30 kg/ m3 respectively. The sampling of Oncorhynchus mykiss blood from the four variants before and after the experimental trial allowed determination of hematological indices. Red blood cell counts (RBCc), hematocrit values (Hct), hemoglobin concentration (Hb), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC) were measured and analyzed, with routine methods used in fish hematology. Differences in hematological parameters were statistically analyzed by Student T test. Physiological stress, induced by maintenance in different technological condition induced by stocking stress, was reflected in the hematological indices (significant increase, p<0.05, RBCc, Hb, Ht, MCV and decrease insignificant, p >0.05 MCH, MCHC) with direct implications at the biotechnological level.